2022
DOI: 10.1113/ep090143
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic responses to heat: From adaptation to maladaptation

Abstract: New Findings What is the topic of this review?This review outlines the history of research on epigenetic adaptations to heat exposure. The perspective taken is that adaptations reflect properties of hormesis, whereby low, repeated doses of heat induce adaptation (acclimation/acclimatization); whereas brief, life‐threatening exposures can induce maladaptive responses. What advances does it highlight?The epigenetic mechanisms underlying acclimation/acclimatization comprise specific molecular programmes on histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…Regardless of the potential functional significance of an increase in total and platelet EVs during heat stress, a new observation of the present analysis is that heat acclimation does not minimize this increase. Animal models have shown that heat adaptation upregulates cytoprotective pathways that lead to greater cellular resilience to various stressors (Murray et al., 2022 ). The cellular adaptations of human heat adaptation are less understood, although several studies have considered elements of the heat shock response (Amorim et al., 2015 ; Hoekstra et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the potential functional significance of an increase in total and platelet EVs during heat stress, a new observation of the present analysis is that heat acclimation does not minimize this increase. Animal models have shown that heat adaptation upregulates cytoprotective pathways that lead to greater cellular resilience to various stressors (Murray et al., 2022 ). The cellular adaptations of human heat adaptation are less understood, although several studies have considered elements of the heat shock response (Amorim et al., 2015 ; Hoekstra et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular responses to heat stress progress along a continuum, from improved cellular thermotolerance following repeated moderate heat exposure to cellular apoptosis during severe heat strain. These cellular outcomes are mediated by intra‐ and extracellular signals, including alarmins, endotoxins, microRNAs and chromatin modifiers (Bouchama et al., 2022 ; Horowitz, 2014 ; Murray et al., 2022 ). Accumulating, albeit still limited, evidence suggests that extracellular vesicles (EVs) might also contribute to cellular signalling and therefore the cellular adaptations in response to heat stress (Bain et al., 2017 ; Bouchama et al., 2008 ; Coombs et al., 2019 ; Wilhelm et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that ambient temperatures on the day of the event were higher than what is typically expected [ 31 ]. The role of heat acclimatization in the pathophysiology of EHS has been investigated, and studies have noted epigenetic adaptations facilitating the regulation of heat shock proteins that protect individuals from heat illness after exposure to heat [ 47 49 ]. In most individuals, adaptations to heat exposure develop during the first 4 days and are completed within 3 weeks [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, unusually warm winters cause a mismatch between seasonal light cycles and temperature cycles that impacted thyroid hormone signalling in mosquitofish ( Gambusia holbrooki ) [91] and caused physiological dysfunction in mice [92]. Similarly, heatwaves can have a broad range of epigenetic effects [93] and caused changes to methylation patterns in a polychaete ( Spiophanes tcherniai ) [85] that can potentially be passed across generations [94].…”
Section: Responses To Environmental Variationmentioning
confidence: 99%